Investigating The Impact of Acquired Fundamental Laboratory Skills in Chemistry on The Student's Actual Academic Achievement in Rutsiro District of Rwanda - IZERE, Elie (SEAMEO QITEP in Science, 2024)
The enhancement of fundamental laboratory abilities in advanced learners has multiple implications for academic performance. Corrective action is necessary for secondary school pupils who are taking chemistry as a core subject because of their poor performance in the subject. The aim of this study was to find out how advanced-level learners learned fundamental laboratory skills in chemistry and how those skills affected their academic performance in two secondary schools. In the investigation, an empirical method was applied. Quantitative data were collected and analysed during the data-gathering processes. From the Rutsiro district of Rwanda, mathematical-chemistry-biology and physics-chemistry-biology combinations in chemistry were studied by a sample of senior five learners in advanced secondary education who were studying chemistry as a core subject. Quantitative data were gathered using a closed questionnaire and a positivist approach that uses deductive research. The theory was the starting point, and it was determined whether or not practical laboratory skills had been established. There were186 respondents in the target group, of which 80 were chosen from several secondary schools, one of which was a boarding school (the School of Excellence) with a fully functional chemical lab and the other a 12-year-old BE (Basic Education) that had chemistry kits but no chemistry lab. The Statistical Package for Social Sciences (SPSS) was used to analyse the data. The results of the paired t-test show that the test mean difference (M = 1.363) is less than the school mean difference (M = 1.463). At the 0.001 level of significance, the results of the analysis suggest that the scores for the two means differed statistically significantly (t (79) = 0.000, n = 80, P < 0.001). The results of the statistical test indicate that students' views towards chemistry were somewhat influenced by the fundamental laboratory chemistry practical skills taught in schools. Students who failed practical tests for basic laboratory skills may not have access to well-equipped labs, but their interest in chemistry can be sustained through practical work.